Efecto del uso como alimento funcional del micelio de Ganoderma curtisii en la estructura del microbioma del tracto digestivo de ratones obesos - Flores Alonso, Rodrigo (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The composition of the intestinal microbiota (MI) is relevant to human health, as the presence of certain microbial groups is associated with the prevention or treatment of chronic diseases and their symptoms. Among the prebiotics that promote the development of beneficial bacteria for health, there are polysaccharides present in the basidiocarp and mycelium of species of the basidiomycete fungi genus Ganoderma. In this study, the effect of dietary supplementation with vegetative mycelium of Ganoderma curtisii was evaluated in a murine model of obesity. A non-obese control group fed a standard diet (DE), an experimental group that received a standard diet supplemented with 100 mg/kg/day of lyophilized mycelium (DEM), an obese group fed a high-fat diet (DAG) (60% of calories from saturated fats), and an obese treated group that received the same high-fat diet supplemented with 100 mg/kg/day of mycelium (DAGM) were used. The composition of the microbiome was determined by DNA sequencing obtained from feces of mice, using the Illumina MiSeq platform to generate paired-end reads (2x276pb) of the V3/V4 regions of the 16S rRNA gene. The results showed that in the DE group, the relative frequency of bacteria from the phylum Firmicutes, Bacteroidetes, and Proteobacteria was 52.0%, 40.3%, and 6.27%, respectively. In the DEM group, a frequency of 30.5%, 64.6%, and 3.57% was observed for phylum Firmicutes, Bacteroidetes, and Proteobacteria, respectively. The DAG group showed that the phylum Firmicutes accounted for 12.3% and Bacteroidetes 18.6%, while Proteobacteria represented 61.2%. Compared to the DAG group, supplementation of the high-fat diet with mycelium, DAGM, practically doubled the content of Firmicutes (26.47%) and Bacteroidetes (40.52%). Additionally, it reduced the content of Proteobacteria by 50% (32.2%).

La composición de la microbiota intestinal (MI) es relevante para la salud humana, ya que la presencia de ciertos grupos microbianos está asociada con la prevención o el tratamiento de enfermedades crónicas y sus síntomas. Entre los prebióticos que promueven el desarrollo de bacterias benéficas para la salud se encuentran los polisacáridos presentes en el basidiocarpo y micelio de especies del género de hongos basidiomicetes Ganoderma. En este estudio, se evaluó el efecto de la suplementación alimenticia con micelio vegetativo de Ganoderma curtisii en un modelo de obesidad en ratón. Se utilizó un grupo control no obeso alimentado con dieta estándar (DE), un grupo experimental que recibió una dieta estándar suplementada con 100 mg/kg/día de micelio liofilizado (DEM), un grupo obeso alimentado con una dieta alta en grasa (DAG) (60% de calorías provenientes de grasas saturadas) y un grupo obeso tratado que recibió la misma DAG, suplementada con 100 mg/kg/día de micelio (DAGM). Se determinó la composición del microbioma, mediante la secuenciación del ADN, obtenido de excreta de ratones, empleando la plataforma Illumina MiSeq para generar lecturas pareadas (reads) 2x276pb, de las regiones V3/V4 del gen de la subunidad 16S de rRNA. Los resultados muestran que en el grupo de DE la frecuencia relativa de bacterias de los phylums Firmicutes, Bacteroidetes y Proteobacterias fue de 52.0%, 40.3% y 6.27%, respectivamente. En el grupo DEM el phylum Firmicutes mostró una frecuencia del 30.5%, Bacteroidetes del 64.6% y Proteobacterias del 3.57%. Para el grupo DAG la frecuencia relativa fue de 12.3% para Firmicutes, de 18.6% para Bacteroidetes y 61.2% para Proteobacteria. Comparado al grupo DAG, la suplementación de la DAG con micelio, DAGM, prácticamente duplicó el contenido de Firmicutes (26.47%) y Bacteroidetes (40.52%); además, redujo en 50% el contenido de Proteobacterias (32.2%).
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2023-0724; Microbiota intestinal; Obesidad; Medios de cultivo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16621